Precautionary Measures Towards Coronavirus Outbreak Management: Situational Awareness, Readiness and Actual-Practice Among Technical Education Members in Universities - Michael , Efuwape B.; Efuwape , Asake O.; Akorede, J. (African Journal of Education,Science and Technology (AJEST), 2021)
Emergence of Corona Virus Pandemic in the global world has heralded a systemic and strategic education on the tragedies associated with the pandemic; giving rise to readiness to fight against the spread and effective practice of standard precautionary measures. This study explores the level of situational awareness, readiness and actual practice of corona virus 2019 pandemic precautions among university staff and students of technical education in Nigeria. The descriptive survey design was guided by 5 hypotheses. The population for the study comprised all staff (academics and technologists) and students in technical education departments across universities in the south-west, Nigeria. A sample of 214 participants comprising 36 academics, 21 technologists and 157 students were drawn through accidental (online survey) sampling technique. A validated questionnaire was used to collect data for the study. The instrument was validated by experts in health education, psychology, measurement and evaluation, and technical education. Data collected was analysed using descriptive statistics, Analysis of Variance, Peason Correlation and Regression Analysis. Findings shows that the influence of readiness (p ˂ .05) is stronger on actual practice of COVID-19 precautionary measures than level of awareness (p ˃ .05). Thus, readiness would play a more major role than awareness in predicting the actual practice of COVID-19 precautionary measures. Hence, awareness campaign should be strengthened with attitudinal or readiness measures to actually facilitate compliance with practice.